Stereodivergent Construction of 1,4‐Nonadjacent Stereocenters via Hydroalkylation of Racemic Allylic Alcohols Enabled by Copper/Ruthenium Relay Catalysis - Chang, Xin; Cheng, Xiang; Liu, Xue‐Tao; Fu, Cong; Wang, Wei‐Yi; Wang, Chun‐Jiang (Angewandte Chemie International Edition, 2022)
An unprecedented hydroalkylation of racemic allylic alcohols and racemic ketimine esters enabled by Cu/Ru relay catalysis has been developed via merging the ruthenium‐catalyzed asymmetric borrowing‐hydrogen reaction with a copper‐catalyzed asymmetric Michael addition in a one‐pot procedure. The current method enables the efficient preparation of highly functionalized δ‐hydroxyesters bearing 1,4‐nonadjacent stereocenters in good yields with high levels of diastereoselectivity and excellent enantioselectivity under mild reaction conditions. The full complement of the four stereoisomers of hydroalkylation products could be readily accessed by orthogonal permutations of two chiral metal catalysts. The current work highlights the power of relay catalysis for the stereodivergent construction of 1,4‐nonadjacent stereocenters that were otherwise inaccessible. An unprecedented stereodivergent hydroalkylation of racemic allylic alcohols and racemic ketimine esters enabled by dual Cu/Ru relay catalysis has been developed. Merging the ruthenium‐catalyzed asymmetric borrowing‐hydrogen reaction with a copper‐catalyzed asymmetric Michael addition into a one‐pot procedure provided a route to highly functionalized δ‐hydroxyesters bearing 1,4‐nonadjacent stereocenters in good yields with excellent stereoselectivity under mild reaction conditions.